Proceedings of the 7th International Power Electronics and Motion Control Conference 2012
DOI: 10.1109/ipemc.2012.6258960
|View full text |Cite
|
Sign up to set email alerts
|

An improved model for the transfer impedance calculations of braided coaxial cables

Abstract: A new model is presented for the accurate predictions of transfer impedance of braided coaxial cables, from a summary study on the earlier models proposed. The complicated responses on the braided shields due to the radiation from the exterior produced electromagnetic fields are taking into account in the new model. In addition, the diameter of braid is rebuilt to improve the accuracy of inductance. The formulas have a close relationship with the primary parameters of braided shield. The accuracy of the new mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Schippers [15], [16] has shown that the magnetic polarizability in the hole inductance models of Vance and Kley is overestimated. In these models, the area of the rhombic aperture is approximated by the surface of an elliptical hole: / 4, e S lw (19) with l the major axis and w the minor axis of the ellipse.…”
Section: ) Schippersmentioning
confidence: 99%
See 3 more Smart Citations
“…Schippers [15], [16] has shown that the magnetic polarizability in the hole inductance models of Vance and Kley is overestimated. In these models, the area of the rhombic aperture is approximated by the surface of an elliptical hole: / 4, e S lw (19) with l the major axis and w the minor axis of the ellipse.…”
Section: ) Schippersmentioning
confidence: 99%
“…3) Wang Xiaoling Another improvement for modelling braid inductance has been proposed by Wang in [16], who calculates M b as follows: . The number of holes υ per unit length is in general large.…”
Section: ) Katakismentioning
confidence: 99%
See 2 more Smart Citations
“…e braided inductance part was introduced by Tyni [4] to improve the accuracy when calculating the transfer impedance of high and low projection coverage cables; Demoulin and Degauque [5] proposed a new model that took into account the effects of additional fluctuations and generated additional attenuation; Marconi et al [6] proposed a test method to measure the transfer impedance of two coaxial cables RG 213 under the same conditions and compared the test results with theoretical calculations; Xiaoling et al [7] proposed a new model for accurately predicting the transfer impedance of braided coaxial cables by summarizing and studying the classical model; Mushtaq and Frei [8,9] introduced the ground plate method (GPM) and capacitive voltage probe (CVP). He compared the test results of the above methods with the triaxial injection method and line injection method.…”
Section: Introductionmentioning
confidence: 99%